La distribution géographique et la présence au Lac-Saint-Jean de toxicodendron radicans (L.) Ktze Var. Rydbergii (small) Erskine - Laverdière, Camille (Cahiers de géographie du Québec, 1961)
The purpose of this paper is to briefly describe the localities of the shrub form of Poison Ivy (Toxicodendron radicansvar. Rydbergii)in the Lake St. John area, and especially to comment upon its displacement from the St. Lawrence plain beyond the Laurentians. We agree with Gillis' use of a former latin binomial name for the plant, we also re-examine the known stations which are plotted on a figure at an appropriate scale this time, and rejecting the persistence of the plant as a relic of the Laflamme Sea period, or as a remnant of an old growth in limey soils, we finally postulate its recent introduction by men or birds.